Triflic Anhydride Promoted Intramolecular Cyclization of N-Aryl Cinnamides: Access to Polysubstituted Quinolin-2(1H)-ones - Zhang, Qian; Yuan, Jingwen; Yu, Mangfei; Zhang, Rui; Liang, Yongjiu; Huang, Peng; Dong, Dewen (Synthesis, 2017)
A facile and efficient synthesis of polysubstituted quinolin-2(1H)-ones is developed via intramolecular cyclization of readily available N-aryl cinnamides promoted by triflic anhydride in N,N-dimethyl trifluoroacetamide (DTA) under mild conditions.
Keywords: C–C bond formation; cyclization reaction; heterocycles; quinolin-2(1H)-ones; triflic anhydride